Adaptively optimized combination (AOC) of magnetic resonance spectroscopy data from phased array coils. Issue 6 (20th July 2015) - Fang, Liang; Wu, Minjie; Ke, Hengyu; Kumar, Anand; Yang, Shaolin
Abstract : Purpose: MR spectroscopy (MRS) can benefit from multi‐element coil arrays with enhanced signal‐to‐noise ratio (SNR). However, how to combine the MRS data in an optimized way from a multi‐element coil array has been studied much less than MRI. A recently published method and routine combination methods have detrimental effects on SNR. We present herein a new method for optimal combination of multi‐coil MRS data. Methods: Based on an analytical solution for maximizing the SNR of the combined spectrum, a new method called "adaptively optimized combination (AOC)" of MRS data from phased array coils was developed in which the inversion of the full noise correlation matrix was incorporated into the coil weighting coefficients. Simulations were carried out to demonstrate the superior performance of the proposed AOC method in various noise scenarios. Validation experiments on human subjects were performed with different voxel locations and sizes on a 3T MRI scanner using an eight‐element phased array head coil. Results: Compared with a recently published method (i.e., weighting with the ratio of signal to the square of noise) and routine methods, our proposed AOC method adaptively and robustly produced significant SNR improvement in the combined spectra. Conclusion: The simulation and human experiments demonstrate that the proposed AOC method represents the theoretical optimal combination of MR spectroscopic data from multi‐element coil arrays. Magn Reson Med 75:2235–2244, 2016. © 2015 Wiley Periodicals, Inc.